Can monetary policy affect the real economy? The dubious effectiveness of interest rate policy - Philip Arestis; Malcolm Sawyer (Levy Economics Institute of Bard College, 2003)
Central bankers and many economists have abandoned activist policies and monetarism and adopted in their place a new view of the role of monetary policy. This view draws on many of the tenets of more traditional theories of money - monetarism's emphasis on inflation control and skepticism about the use of easy-money policies to permanently increase output, and the Keynesian view that the total stock of money is not an important driving force behind either inflation or unemployment - yet it also takes a dim view of democratic input to the policymaking process. This brief evaluates a premise subscribed to by most central bankers: that monetary policy can be effectively used to control inflation without any permanent sacrifice in the form of reduced income or job opportunities.
Keywords: 330; Geldpolitik; Transmissionsmechanismus